Asymmetric stepwise reductive amination of sulfonamides, sulfamates, and a phosphinamide by nickel catalysis - Zhao, Xiaohu (2021)
Asymmetric reductive amination of poorly nucleophilic sulfonamides was realized in the presence of nickel catalysts and titanium alkoxide. A wide range of ketones, including enolizable ketones and some biaryl ones, were converted into sulfonamides in excellent enantiomeric excess. The cyclization of sulfamates and intermolecular reductive amination of a diarylphosphinamide were also successful. Formic acid was used as a safe and economic surrogate of high-pressure hydrogen gas.